Noodles: Testing for Quality - Solah, Vicky; Crosbie, G. (2015)
© 2016 Elsevier Ltd. All rights reserved. Sensory evaluation and instrumental methods for testing noodle quality are important for flour mill quality control and organizations involved in noodle research or the evaluation of new noodle wheat varieties. The preparation of noodles for sensory evaluation and subsequent instrumental testing that is related to visual and textural characteristics involves the incorporation of theory and the guidelines provided by experienced researchers in these areas.